2014
DOI: 10.1021/jm500510f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (S)-1-(1-(Imidazo[1,2-a]pyridin-6-yl)ethyl)-6-(1-methyl-1H-pyrazol-4-yl)-1H-[1,2,3]triazolo[4,5-b]pyrazine (Volitinib) as a Highly Potent and Selective Mesenchymal–Epithelial Transition Factor (c-Met) Inhibitor in Clinical Development for Treatment of Cancer

Abstract: HGF/c-Met signaling has been implicated in human cancers. Herein we describe the invention of a series of novel triazolopyrazine c-Met inhibitors. The structure-activity relationship of these compounds was investigated, leading to the identification of compound 28, which demonstrated favorable pharmacokinetic properties in mice and good antitumor activities in the human glioma xenograft model in athymic nude mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 19 publications
1
85
0
Order By: Relevance
“…Combining osimertinib with an agent active on an alternative signaling pathway such as selumetinib (MEK1/2 inhibitor; AZD6244, ARRY-142886) 10 or savolitinib (MET-TKI; AZD6094, HMPL-504, volitinib) 11 may enhance activity in patients with acquired resistance to EGFR-TKIs, or delay the development of subsequent resistance via these alternate routes. Combining EGFR-TKIs with an immune-mediated therapy, such as durvalumab [anti-programmed cell death ligand 1 (anti-PD-L1) monoclonal antibody, MEDI4736], 12 may enhance antitumor immunity through downregulation of PD-L1, as EGFR activation has been shown to induce PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Combining osimertinib with an agent active on an alternative signaling pathway such as selumetinib (MEK1/2 inhibitor; AZD6244, ARRY-142886) 10 or savolitinib (MET-TKI; AZD6094, HMPL-504, volitinib) 11 may enhance activity in patients with acquired resistance to EGFR-TKIs, or delay the development of subsequent resistance via these alternate routes. Combining EGFR-TKIs with an immune-mediated therapy, such as durvalumab [anti-programmed cell death ligand 1 (anti-PD-L1) monoclonal antibody, MEDI4736], 12 may enhance antitumor immunity through downregulation of PD-L1, as EGFR activation has been shown to induce PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…AZD6094 (savolitinib, HMPL-504) is a novel, potent, and selective MET inhibitor currently in clinical development in various indications, including PRCC (11,12). In preclinical studies, AZD6094 displayed nanomolar in vitro activity against MET and its downstream signaling targets.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling showed that the mutant c-MET was sufficiently distorted to prohibit the binding of the drug. SAVOLITINIB (volitinib, AZD6094) was synthesized by AstraZeneca as a Type I specific c-MET inhibitor [150] and shown initially to be active against gastric and renal cancers xenograft models [151,152]. The drug was subsequently shown to be active against NSCLC models both in vivo and in vitro where it also targets PI3K and MAPK [153].…”
Section: Hepatocyte Growth Factor Receptor (Hfgr C-met)mentioning
confidence: 99%